Building your New Testament Greek vocabulary - Van Voorst, Robert E. (Resources for biblical study, 2001)
"Building Your New Testament Greek Vocabulary, now in its third edition, provides students a user-friendly introduction to the basic vocabulary of New Testament Greek. Robert Van Voorst helps the student to move away from rote memorization toward better long-term vocabulary learning based on how Greek words are built and related to each other. He provides students with easy-to-remember English derivatives, lists the number of occurrences for each word learned, and provides lists that are easily learned in a single vocabulary-learning session. Most importantly, he organizes this book on the basis of word families and frequency. New to this edition are a comprehensive list of proper nouns and a section to help students understand aytos and similar words. Definitions of Greek words have been revised where necessary according to the new, third edition of the Greek-English Lexicon of the New Testament edited by Frederick Danker."--Jacket